Effect of the leukotriene receptor antagonist MK-0679 on baseline pulmonary function in aspirin sensitive asthmatic subjects. Issue 12 (December 1993) - Dahlén, B; Margolskee, D J; Zetterström, O; Dahlén, S E
Abstract : BACKGROUND–The cysteinyl leukotrienes (LTC4, LTD4, and LTE4) have been shown to mediate airway obstruction evoked by several factors which trigger asthmatic reactions–for example, allergen and exercise. Accordingly, drugs which block the action or formation of these leukotrienes are being evaluated as a new treatment of asthma. Elevated production of leukotrienes has been reported in asthmatic subjects who are intolerant to aspirin and related nonsteroidal anti-inflammatory drugs. In this study the influence of the specific leukotriene receptor antagonist MK-0679 was tested on basal airway function in asthmatic patients with documented aspirin intolerance. METHODS–The eight subjects in the study had a mean baseline FEV1 of 78% predicted (range 58-99%) and six required treatment with inhaled glucocorticosteroids (400-1200 micrograms budesonide/beclomethasone daily). On two separate days the subjects received either 825 mg MK-0679 or placebo, orally in a double blind, randomised, crossover design. RESULTS–The leukotriene antagonist MK-0679 caused bronchodilation which lasted for at least nine hours. The average peak improvement in FEV1 was 18% above the predrug baseline, but the bronchodilator response varied between 34% and 5% and was found to correlate strongly with the severity of asthma and aspirin sensitivity. CONCLUSIONS–The findings indicate that ongoing leukotriene production may be one cause of persistent airway obstruction in aspirin sensitive asthmatic subjects and that they may benefit from treatment with a leukotriene receptor antagonist.